Identification of HER2 Immunohistochemistry-Negative, FISH-Amplified Breast Cancers and Their Response to Anti-HER2 Neoadjuvant Chemotherapy. Issue 2 (18th October 2018) - Gibbons-Fideler, I-sanna; Nitta, Hiroaki; Murillo, Adrian; Tozbikian, Gary; Banks, Peter; Parwani, Anil V; Li, Zaibo
Abstract: Objectives: Either immunohistochemistry (IHC) or in situ hybridization (ISH) can be used to determine human epidermal growth factor receptor 2 (HER2) status. Breast cancers (BCs) with HER2 IHC-negative (IHC–) and ISH-amplified (ISH+) results have been rarely reported but not well studied. We investigated the frequency of HER2 IHC–/ISH+ BCs and their response to anti-HER2 neoadjuvant chemotherapy (NAC). Methods: Seventeen BCs with HER2 IHC–/ISH+ results were identified from 1, 107 consecutive invasive BCs (1.5%, 17/1, 107). Results: Gene protein assay confirmed the original HER2 IHC and ISH results. Increased HER2 RNA level was detected in HER2 IHC–/ISH+ cases compared with HER2 IHC–/ISH– cases. Eight patients had anti-HER2 NAC; three had pathologic complete response, and five had residual tumors. Conclusions: A small percentage of patients (1.5%) showed discordant HER2 IHC and ISH results (IHC–/ISH+) and would have lost the opportunity for potentially beneficial anti–HER2-targeted therapy if only HER2 IHC testing had been used.